UJI DAYA ANTIINFLAMASI EKSTRAK ETANOLIK KULIT TERONG BELANDA (Solanum betaceum, Cav.) PADA MENCIT JANTAN YANG DIINDUKSI KARAGENIN - Margareta Retno Priamsari; Rina Ayu Krismonikawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACT Inflammation is a normal response to injury due to release of chemical mediators such as prostaglandins. Solanum betaceum Cav. skin contains flavonoid compounds. This study aims to determine the antiinflammatory power and the effect of variations in the dose of ethanolic extract of the skin of Solanum betaceum Cav on Swiss male strain mice caragenin-induced. The ethanolic extract of Solanum betaceum Cav skin was obtained using remaseration method with 96% ethanol solvent. Antiinflammatory power test using edema formation method with induction of caragenin 1% intraplantar 30 minutes before administration of the test material. Tests were carried out on 25 mice records which were divided into 5 groups namely negative control (0.5% CMC Na suspension), positive control (diclofenac sodium suspension in 0.5% CMC Na dose 7 mg/kgBW) and given suspension respectively. Dutch eggplant skin ethanolic extract in CMC Na 0.5% dose 70 mg/kgBW; 140 mg/kgBW; 280 mg/kgBW orally. The parameters observed were edema thickness measured using calipers at 30 minute intervals for 360 minutes. The results of edema thickness difference are used to calculate the Area Under Curve (AUC) and the percentage of antiinflammatory power (% AIP). Dat a were analyzed statistically with the One Way Anova test and continued by the Post Hoc Test with a 95% confidence level. The results showed that the ethanolic extract of Solanum betaceum Cav skin contains flavonoid compounds and has antiinflammatory power. The greater the dose of ethanolic extract of Solanum betaceum Cav skin, the greater the anti-inflammatory power. Keywords: Solanum betaceum Cav., antinflammation, caragenin